INTEGRATION OF ROCK PHYSICS, PETROPHYSICS AND SEISMIC ATTRIBUTES IN REDUCING UNCERTAINTIES FOR BETTER FACIES DELINEATION AND HYDROCARBON PRORPERTIES - MURUTHY, SAMINI PANDIAN (2020)
An integrated reservoir characterization engages with the working of models illustrative of subsurface geological formations, which are then used to predict and optimize oil and gas production. To be known single discipline can’t give a full depiction of the reservoir characteristics. In order to create the most comprehensive reservoir understanding, an integrated reservoir properties has turned out to be progressively important. One of the important properties is the acoustic impedance, an elastic parameter that usually delineate shale and reservoir sand. It has been very beneficial for hydrocarbon exploration. Conversely not always this property would be able to delineate the fluid and lithology due to inconsistent range of values they might produce.